(untitled) (Relaciones Internacionales, 2019)
This paper focuses on discussing and analyzing strategic alliances in order to understand whether they are a foreign policy option for Latin American States or just a discursive strategy. The main objective is to attain a better understanding of strategic alliances with respect to their main goals and expectations, analyzing whether they are short or long-term options, and evaluating how many strategic alliances a single country is able to develop. The central argument is that, in many cases, although Latin American leaders state the existence of strategic partnerships in their mutual relations, there is still a gap between discourse and practice. This situation implies the risk of removing the concept of the content.